Universal Health Coverage and Hospital Service Satisfaction in Socio-Economically Vulnerable Tourism Areas - Nurillah Agustina; Rahmad Hidayat; Ariy Dermawan; Ayatullah Hadi (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2025)
This study examines the implementation of Universal Health Coverage (UHC) at the Mataram City General Hospital—a referral facility situated in a socio-economically vulnerable, tourism-dependent area of West Nusa Tenggara, Indonesia. Service quality is assessed across three dimensions: (1) administrative service quality, (2) accessibility of health services, and (3) clinical service quality, framed against the challenges of achieving SDG 3 (Good Health and Well-Being), SDG 1 (No Poverty), and SDG 10 (Reduced Inequalities). Using a descriptive qualitative design, we conducted interviews, observations, and document analysis, and coded the data in NVivo 12 Plus. Findings indicate that administrative processes have improved in clarity, speed, and ease of registration; however, responsiveness and lengthy waiting times persist. Digital platforms have enhanced access, yet geographical barriers and a digital divide continue to constrain equity. Overall clinical quality is satisfactory but limited by insufficient empathy and suboptimal communication from health workers. The study contributes empirically by showing how systemic constraints—uneven resource allocation, workforce shortages, and infrastructure deficits—undermine UHC objectives in vulnerable, tourism-reliant settings. Policy implications include the need for area-based planning, stronger inter-agency coordination, and context-sensitive innovation to deliver more equitable and inclusive services across West Nusa Tenggara.